A micromechanical model of filled elastomers based on the directional hydrodynamic strain amplification factor. Issue 1 (17th December 2018) - Darabi, Ehsan; Itskov, Mikhail; Klüppel, Manfred
Abstract: A constitutive model for filled elastomers is proposed based on the combination of the continuum damage [1] and the dynamic flocculation [2] framework. Damage takes place in both the network rubbery matrix and inside the filler aggregates. Accordingly, the probability density functions of the number of segments and the filler size distribution in all spatial directions evolve with deformation, which causes stress softening, the Mullins effect and induced anisotropy. Multiple breakage and reaggregation of filler clusters with different sizes in various spatial directions are the main sources of the directional hydrodynamic strain amplification. The model includes a few number of physically motivated material constants characterizing the average filler cluster dimension, filler‐filler and filler‐matrix interaction properties.